Opposing effects of bile acids deoxycholic acid and ursodeoxycholic acid on signal transduction pathways in oesophageal cancer cells. Issue 5 (September 2016) - Abdel-Latif, Mohamed M.; Inoue, Hiroyasu; Reynolds, John V.
Abstract : Ursodeoxycholic acid (UDCA) was reported to reduce bile acid toxicity, but the mechanisms underlying its cytoprotective effects are not fully understood. The aim of the present study was to examine the effects of UDCA on the modulation of deoxycholic acid (DCA)-induced signal transduction in oesophageal cancer cells. Nuclear factor-κB (NF-κB) and activator protein-1 (AP-1) activity was assessed using a gel shift assay. NF-κB activation and translocation was performed using an ELISA-based assay and immunofluorescence analysis. COX-2 expression was analysed by western blotting and COX-2 promoter activity was assessed by luciferase assay. DCA induced NF-κB and AP-1 DNA-binding activities in SKGT-4 and OE33 cells. UDCA pretreatment inhibited DCA-induced NF-κB and AP-1 activation and NF-κB translocation. This inhibitory effect was coupled with a blockade of IκB-α degradation and inhibition of phosphorylation of IKK-α/β and ERK1/2. Moreover, UDCA pretreatment inhibited COX-2 upregulation. Using transient transfection of the COX-2 promoter, UDCA pretreatment abrogated DCA-induced COX-2 promoter activation. In addition, UDCA protected oesophageal cells from the apoptotic effects of deoxycholate. Our findings indicate that UDCA inhibits DCA-induced signalling pathways in oesophageal cancer cells. These data indicate a possible mechanistic role for the chemopreventive actions of UDCA in oesophageal carcinogenesis.